Perilaku Mahasiswi Dalam Perawatan Kecantikan Secara Tradisional - Indarto A S; Nutrisia Aquariushinta Sayuti; Atik Riwati (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Behavior, Young Women, Traditional Beauty Care. This study aims to reveal the behavior of a student in a traditional beauty treatments. This study used a qualitative design with sampling technique is purposive sampling and the type of maximum variation sampling. Collecting data using Focus Group Discussion and Interview depth. This study uses 6 informant DKT and 2 informants WM. Test the validity of the data was done by using triangulation. The results showed that most informants understand the sense of beauty treatments and traditional, benefits and problems on the part of the body, the informant also shows a good attitude to the traditional beauty treatments, and the attitude of informants in beauty treatments traditionally reaches levels responsible attitude. Activity informant in beauty treatments has traditionally been reached on the level of activity adoption.